2019
DOI: 10.3389/fneur.2019.00693
|View full text |Cite|
|
Sign up to set email alerts
|

HTRA1 Mutations Identified in Symptomatic Carriers Have the Property of Interfering the Trimer-Dependent Activation Cascade

Abstract: Background: Mutations in the high-temperature requirement A serine peptidase 1 (HTRA1) cause cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL). Most carriers for HTRA1 mutations are asymptomatic, but more than 10 mutations have been reported in symptomatic carriers. The molecular differences between the mutations identified in symptomatic carriers and mutations identified only in CARASIL patients are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…The youngest and oldest reported ages at onset of neurological symptoms/signs among symptomatic carriers were 29 (25) and 77 (30), respectively, and the youngest and oldest ages at onset (7,18,26).…”
Section: Comparison Of Symptomatic Carrier and Carasil Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The youngest and oldest reported ages at onset of neurological symptoms/signs among symptomatic carriers were 29 (25) and 77 (30), respectively, and the youngest and oldest ages at onset (7,18,26).…”
Section: Comparison Of Symptomatic Carrier and Carasil Clinical Featuresmentioning
confidence: 99%
“…It thus remains unclear why certain mutations cause CSVD in HTRA1 carriers. Previously, we reported that either a deficiency in trimerization or an amino-acid mutation located in the loop D (LD) or loop 3 (L3) domain was common in missense HTRA1 proteins identified in symptomatic carriers (18). We speculated that these mutations in the HTRA1 gene may inhibit wild-type (WT) protease activity (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, some mutations identified in manifested carriers did not show dominant-negative effects (4,5,11). In these cases, haploinsufficiency, which often results in reduced penetrance and variable expressivity, may explain the occurrence of cerebral SVD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have experimentally demonstrated that certain missense mutant HTRA1 proteins show a marked decrease in protease activities as well as reduced wild-type HTRA1 activity, presumably due to interference in the trimer-dependent activation cascade of the enzyme. Recently, two different mechanisms were proposed to underlie the dominant-negative effects of HTRA1 mutations (4,11): the inhibition of trimer formation, and the inhibition of the wild-type HTRA1 activity, observed in several missense mutations located in the sensor domain of loop 3 (L3) or the activation domain of loop D (LD) of HTRA1. These two domains play an essential role in the normal protease activity of HTRA1 (10,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation